Caracterización antigénica In Silico de las proteínas de unión a la fibronectina A y B, y del factor de aglutinación A de Staphylococcus aureus como candidatos vacunales para la prevención de mastisis subclínica en Bos taurus (2020)
In silico approach of vaccine candidates for Staphylococcus aureus that causes subclinical mastitis in Bos taurus was carried out. This, by bioinformatic analysis of sequences from fibronectin B binding proteins and the agglutination factor A genes, this sequences obtained from S. aureus strains from the Agrosavia collection of Microorganisms of interest in animal health. Subsequently, reported sequences of these proteins were included in the analysis and, additionally, reported sequences of the fibronectin A binding protein. Through predictions of the secondary and tertiary structure of these proteins, in addition to the analysis of the interaction with the respective ligands and predictions of antigenicity of the proteins, antigenic domains were identified. Finally, the prediction of candidate epitopes capable of generating a humoral response that allows preventing cases of subclinical mastitis was carried out.